A Critical Perspective of Transaction Cost Economics: the case of the Inquiry Committee into Oil-for-Food Program Scandal - Da Veiga, M. R.; Major, M. (European Institute for Advanced Studies in Management, 2015)
This paper demonstrates that Transaction Cost Economics (TCE) alignment hypothesis did not verify insofar “probity” hazards – “ethics” – cannot be relieved by governance structures, as predicted in the case of the inquiry into the United Nations (UN) Oil-For-Food Programme (OFFP) scandal. The inquiry, which contains “sovereign” as well as “quasi-judiciary” transactions’ elements, and though lack the “authority of the sovereign” and the “independence” of the judiciary attributes, did not achieve its stated purposes. We apply Williamson’s TCE theory (1999) and McCloskey’s (2006) “virtues ethics” to the questions: i) has the inquiry worked? ii) has TCE’s discriminating alignment hypothesis been verified in the case of the OFFP scandal inquiry? The longitudinal historical narrative analytical case based research covering more than 20 years of history was developed to address decisions of oversight governance structures at the UN in the context of systemic failures of probity / ethics. The UN took adaptive ex post action and reformed internal oversight governance structures in a movement that might have been devised mainly to help rebuild reputation and secure funding continuation but which intrinsically changed little. We argue that TCE should be modified to include McCloskey’s “virtues ethics” behavioral dimension as a transaction costs’ reduction device and an explanatory framework for bureaucratic ethical failures. Key